Research on occupational diseases in the absence of occupational data: a mixed-method study among cancer registries of Western Switzerland (Swiss Medical Weekly, 2022)
The contribution of occupation-related diseases to the global burden of disease is greatly underestimated, mainly due to a shortage of occupational exposure data. This problem is particularly salient in Switzerland, where no estimates of occupation-related disease burden exist, even for the well-recognised occupational cancers, such as malignant pleural mesothelioma and lung cancer.To overcome this situation, we launched a research project “Examining Cancers and Labour Indicators to assess the Burden” (ExCaLIBur). Within this project, we aimed to assess the need for and quality (i.e., completeness, accuracy and precision) of occupation registration in all cancer registries of Western Switzerland. We also aimed to find a relevant and feasible strategy to collect this information in the future.We applied a mixed research method. We observed that, independently of the level of precision (5-3-2-1-digit aggregation level), the accuracy was lesser in the registries that were able to actively search and verify occupational information. Overall, the distinction of occupations based on the 3-digit code presents an acceptable compromise in terms of precision. Having such occupations registered in all, or most, Swiss cancer registries routinely would obviously be valuable for epidemiological surveillance of occupational cancers in Switzerland. However, it seems less obvious how these data could fulfill the research objectives, since a better precision than 3-digit occupational coding is challenging to achieve.Currently, the collection of occupational data by the Swiss cancer registries remains feasible in the frame of specific research projects on occupational cancers. However, available data sources, as well as lack of financial and human resources, will continue to affect quality of the collected occupation data. Therefore, the usage of the standardised questionnaire retracing the individual occupational history to enable further assessment of individual exposure to potential occupational hazards is recommended. However, this approach will disable the Swiss registries to insuring their epidemiological surveillance mission with respect to occupational cancers in Switzerland, for which national statistics remain limited.